Development and evaluation of an up-converting phosphor technology-based lateral flow assay for the rapid, simultaneous detection of Vibrio cholerae serogroups O1 and O139. - Min Hao; Pingping Zhang; Baisheng Li; Xiao Liu; Yong Zhao; Hailing Tan; Chongyun Sun; Xiaochen Wang; Xinrui Wang; Haiyan Qiu; Duochun Wang; Baowei Diao; et al. (PLoS ONE)
Vibrio cholerae serogroups O1 and O139 are etiological agents of cholera, a serious and acute diarrheal disease, and rapid detection of V. cholerae is a key method for preventing and controlling cholera epidemics. Here, a point of care testing (POCT) method called Vch-UPT-LF, which is an up-converting phosphor technology-based lateral flow (UPT-LF) assay with a dual-target detection mode, was developed to detect V. cholerae O1 and O139 simultaneously from one sample loading. Although applying an independent reaction pair made both detection results for the two Vch-UPT-LF detection channels more stable, the sensitivity slightly declined from 104 to 105 colony-forming units (CFU) mL-1 compared with that of the single-target assay, while the quantification ranges covering four orders of magnitude were maintained. The strip showed excellent specificity for seven Vibrio species that are highly related genetically, and nine food-borne species whose transmission routes are similar to those of V. cholerae. The legitimate arrangement of the two adjacent test lines lessened the mutual impact of the quantitation results between the two targets, and the quantification values did not differ by more than one order of magnitude when the samples contained high concentrations of both V. cholerae O1 and O139. Under pre-incubation conditions, 1×101 CFU mL-1 of V. cholerae O1 or O139 could be detected in fewer than 7 h, while the Vch-UPT-LF assay exhibited sensitivity as high as a real-time fluorescent polymerase chain reaction with fewer false-positive results. Therefore, successful development of Vch-UPT-LF as a dual-target assay for quantitative detection makes this assay a good candidate POCT method for the detection and surveillance of epidemic cholera.